Astatine-211 radiolabelling chemistry: from basics to advanced biological applications - Maarten Vanermen; Mathilde Ligeour; Maria-Cristina Oliveira; Jean-François Gestin; Filipe Elvas; Laurent Navarro; François Guérard (SpringerOpen, 2024)
Abstract Background 211At-radiopharmaceuticals are currently the subject of growing studies for targeted alpha therapy of cancers, which leads to the widening of the scope of the targeting vectors, from small molecules to peptides and proteins. This has prompted, during the past decade, to a renewed interest in developing novel 211At-labelling approaches and novel prosthetic groups to address the diverse scenarios and to reach improved efficiency and robustness of procedures as well as an appropriate in vivo stability of the label. Main body Translated from the well-known (radio)iodine chemistry, the long preferred electrophilic astatodemetallation using trialkylaryltin precursors is now complemented by new approaches using electrophilic or nucleophilic At. Alternatives to the astatoaryl moiety have been proposed to improve labelling stability, and the range of prosthetic groups available to label proteins has expanded. Conclusion In this report, we cover the evolution of radiolabelling chemistry, from the initial strategies developed in the late 1970's to the most recent findings.